FCC waste catalyst synthesized bundle filamentous ZSM-48 molecular sieve with low silica-alumina ratio and preparation method thereof

By using FCC waste catalyst to prepare low silicon-aluminum ratio ZSM-48 molecular sieve, the problems of high silicon-aluminum ratio, low acid amount and high synthesis cost in the prior art are solved, efficient and low-cost synthesis are achieved, and catalytic performance is improved.

CN119569078AActive Publication Date: 2025-03-07CHINA CATALYST HLDG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411465905.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-07
Estimated Expiration
2044-10-21

Smart Images

  • Figure CN119569078A_ABST
    Figure CN119569078A_ABST
Patent Text Reader

Abstract

The invention discloses a FCC waste catalyst synthesized bundle filamentous ZSM-48 molecular sieve with a low silica-alumina ratio and a preparation method thereof.The ZSM-48 bundle filamentous molecular sieve is prepared by taking FCC waste catalyst particles as part of raw materials, a template agent and an auxiliary agent through a hydrothermal crystallization reaction, in obtained bundle filamentous molecular sieve crystals, the diameter of bundle filaments is 1-2 microns, the length of the bundle filaments is 2-20 microns, the diameter of monofilaments in the bundle filaments is 10-20 nm, and the diameter of the monofilaments in the bundle filaments is 10-20 nm. The bundled crystals are stacked and well dispersed, and the molar ratio of silicon oxide to aluminum oxide in the molecular sieve ranges from 24 to 100. The ZSM-48 molecular sieve can be prepared into a molecular sieve catalyst to be applied to dewaxing catalytic reaction of alkane-containing raw materials, can also be applied to the fields of n-alkane hydroisomerization, long-chain alkane hydrocracking, C4-olefin cracking, xylene isomerization, conversion of methanol into gasoline (MTG), preparation of hydrocarbon from methanol, direct conversion of synthesis gas (CO + H2) into gasoline and the like, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a FCC waste catalyst synthesis bundle filamentary low silicon-aluminum ratio ZSM-48 molecular sieve and a preparation method thereof, belonging to the technical field of inorganic material synthesis. Background Art

[0002] ZSM-48 molecular sieve is a new type of high-silicon molecular sieve synthesized by Mobil Corporation in the United States in the early 1980s. It has a one-dimensional ten-membered ring opening with a non-through and interlaced two-dimensional linear channel with an MRE topological structure. The channels are connected by 5-membered rings, and its ideal channel diameter is 0.53nm×0.56nm. Due to its unique one-dimensional ten-membered ring straight-through channel structure and appropriate acid content, it is widely used in normal alkane hydroisomerization, long-chain alkane hydrocracking, C4-olefin cracking, xylene isomerization, methanol to gasoline (MTG), methanol to hydrocarbons and synthesis gas (CO+H2) direct conversion to gasoline, etc. In the process of n-alkane hydrogenation isomerization reaction, the isomerization reaction of n-alkane mainly occurs at the ten-membered ring pore of the carrier ZSM-48 molecular sieve. Therefore, the acid center located at the pore mouth is conducive to the performance improvement of the isomerization reaction. The acidity in the pore channel will cause cracking side reactions due to its strong acidity and the limitation of its own diffusion in the pore channel, thereby affecting the isomer yield. In the catalytic reaction, however, the conventional ZSM-48 molecular sieve currently has problems such as high silicon-aluminum ratio, low acid content and high synthesis cost. Therefore, the development of a low-cost synthesis method of low silicon-aluminum ratio ZSM-48 molecular sieve has very important practical significance.

[0003] US5075269 discloses that water glass and silica sol are used as silicon sources, aluminum sulfate and sodium aluminate are used as aluminum sources, and hexamethylammonium bromide is used as a template agent to synthesize a ZSM-48 molecular sieve with a silicon-aluminum ratio as low as 170. CN112142066A discloses a ZSM-48 molecular sieve composed of a double template agent HMDA and CTAC, and after aging and hydrothermal crystallization, a silicon-aluminum ratio range of 80-600 is obtained. CN101330976B discloses the use of an organic template of hexamethylammonium salt to obtain a ZSM-48 molecular sieve having a silicon-to-aluminum ratio of 70 to 110; US7625478 and US7482300 disclose the use of expensive hexamethylammonium bromide as a template and ZSM-48 as a seed crystal, which can be crystallized for 48 hours with a silicon-to-aluminum ratio of about 100 and a minimum SiO2 / Al2O3 molar ratio of 80 to obtain a ZSM-48 molecular sieve, but there are also problems of high cost and high pollution.

[0004] FCC catalysts are usually composed of zeolite Y ion-exchanged with rare earth elements (lanthanum or cerium), an inert matrix of kaolin, and a binder mixed with silica and alumina. During the FCC reaction, the generation of coke deposits will lead to clogging of catalyst pores and deactivation of active sites. The mainstream disposal method of FCC waste catalysts is collection and landfill, which may cause secondary pollution of soil and groundwater. Although it can obtain certain economic benefits by extracting valuable metals from FCC waste catalysts through methods such as hydrometallurgy and treating waste catalysts to reduce toxicity, it will still produce secondary hazardous solid wastes. This kind of FCC waste catalyst contains a large amount of silicon and aluminum elements, especially the Y or USY molecular sieve structure can provide four-membered ring and six-membered ring secondary structural units, which are easily reorganized into the unit structure of ZSM-48 molecular sieve during the crystallization process, forming a special morphology with low silicon-aluminum ratio characteristics, which not only makes full use of resources, but also reduces the synthesis cost and obtains special molecular sieve products with better performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor relative crystallinity of ZSM-48 molecular sieve and inability to obtain a low silicon-aluminum ratio in the prior art, and to provide a FCC waste catalyst as a silicon-aluminum source to synthesize a bundle-shaped low silicon-aluminum ratio ZSM-48 molecular sieve and a preparation method thereof. The preparation method of the ZSM-48 molecular sieve can re-crystallize and utilize most of the silicon-aluminum sources in the FCC waste catalyst, is simple to operate, has high production efficiency, and is conducive to industrial production. The obtained ZSM-48 molecular sieve has a high relative crystallinity and is applied to hydrocarbon oil hydroisomerization reaction to obtain a higher product yield.

[0006] The ZSM-48 molecular sieve in the existing synthesis technology is generally in an aggregated state and has large crystals. When the ZSM-48 molecular sieve is used for catalytic reactions, the diffusion resistance of the reactant or product molecules on the surface of the molecular sieve crystal is large, carbon deposition is easily generated, and it is difficult to apply it on a large scale in industry. Therefore, it is of great significance to synthesize a single crystal phase, a small particle size, a large specific surface area, and a non-aggregated morphology of ZSM-48 molecular sieve.

[0007] In order to solve the above technical problems, the technical solution of the present invention is: a bundled filament ZSM-48 molecular sieve, in which the diameter of the bundled filaments is 1-2 μm, the length of the bundled filaments is 2-20 μm, the diameter of the single filaments in the bundled filaments is 10-20 nm, and the molar ratio of silicon oxide to aluminum oxide is 24-100. The preparation steps include: 1) The FCC waste catalyst particles are crushed into small particles of 80-120 mesh, calcined at 600-1000 °C for 1-10 hours, and the calcined solid is ultrasonically soaked in 0.1-1.0 mol / L hydrochloric acid, sulfuric acid or nitric acid solution at a solid-liquid ratio of 1: (4-10) for 1-5 hours, filtered, washed with deionized water until the pH value reaches 6-8, and dried to obtain a silicon-alumina powder with a dry basis ≥75%.

[0008] 2) The silicon-aluminum powder obtained in 1) is mixed with a silicon source, an alkali source and deionized water, and aged at 80-120°C for 12-36 hours, and an organic template agent OSDA and an auxiliary agent AIDS are added, and crystallized at 150-200°C for 24-120 hours, and the bundled filamentous ZSM-48 molecular sieve is obtained after quenching and recovery.

[0009] Silicon is calculated as silicon oxide, aluminum is calculated as aluminum oxide, alkali source is calculated as sodium oxide, and n SiO2 / n Al2O3 20~100, n NaO2 / n SiO2 0.03~0.08, n H2O / n SiO2 15~60, n OSDA / n SiO2 0.03~0.3, n AIDS / n SiO2 It is 0.001~0.01.

[0010] The organic template is [(R1)3N + (CH2)n N + (R2)3]·2X - , R1 and R2 are each independently a C1-C5 straight chain alkyl group, n is an integer of 3-10, X - OH - , Cl - Br - ,I - At least one of .

[0011] The auxiliary agent is any one or more of ethanolamine, N,N-dimethylethanolamine, N-methylmonoethanolamine, N-ethylethanolamine, and N, N-dimethylisopropanolamine.

[0012] In some specific filamentary ZSM-48 molecular sieves, R1 and R2 are independently methyl, ethyl, n-propyl or n-butyl, n is an integer of 4-8, and X is OH - , Cl - Br - or I - Any one of .

[0013] Some specific filamentary ZSM-48 molecular sieves, R1 and R2 are methyl, X is OH - Or Br - .

[0014] In some specific filamentous ZSM-48 molecular sieves, the silicon source is one or more of silica sol, water glass, C-type silica gel, macroporous silica gel, coarse-porous silica gel, fine-porous silica gel, white carbon black, chromatography silica gel, diatomaceous earth and organosilane.

[0015] For some specific filamentary ZSM-48 molecular sieves, the organosilane is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, ethyltriethoxysilane, vinyltriethoxysilane, triethoxysilane, propyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane, methyltriethoxysilane, trimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, methyldimethoxysilane, isobutyltriethoxysilane, diisopropyldimethoxysilane, and isobutylisopropyldimethoxysilane.

[0016] For some specific filamentary ZSM-48 molecular sieves, the organosilane is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, trimethoxysilane and triethoxysilane.

[0017] Some specific filamentary ZSM-48 molecular sieves, n SiO2 / n Al2O3 25~100, n NaO2 / n SiO2 0.035~0.08, n H2O / n SiO2 15~55, n OSDA / n SiO2 0.035~0.25, n AIDS / n SiO2 It is 0.0015~0.0095.

[0018] Some specific filamentary ZSM-48 molecular sieves have a molar ratio of silicon oxide to aluminum oxide ranging from 24 to 100.

[0019] The above-mentioned application of the filamentous ZSM-48 molecular sieve in the hydrocarbon oil hydroisomerization reaction.

[0020] A process for synthesizing a bundled filamentary low silicon-aluminum ratio ZSM-48 molecular sieve from FCC waste catalyst, the preparation steps are as follows: 1) The FCC waste catalyst particles are crushed and sieved to obtain small particles of 80-120 mesh, and then calcined at 600-1000°C for 1-10 hours to remove carbon deposits and attached organic matter. The solid product after calcination is ultrasonically soaked in 0.1-1.0 mol / L hydrochloric acid or sulfuric acid or nitric acid solution at a solid-liquid ratio of 1: (4-10) for 1-5 hours, and the recovered material is filtered and washed with deionized water to a pH value of 6-8, and the filter cake is dried at 100-150°C to obtain a dry basis ≥75% silicon aluminum powder for standby use.

[0021] 2) After mixing the silicon-aluminum powder obtained in 1) with silicon source, alkali source and deionized water, the slurry is SiO2 / n Al2O3 The ratio is 20~100, n NaO2 / n SiO2 The ratio is 0.03~0.08, n H2O / n SiO2 The mixture is aged in a hydrothermal synthesis reactor at 80-120°C for 12-36 hours, and an organic template (OSDA) and an auxiliary agent (AIDS) are added to the mixture so that n OSDA / n SiO2 The ratio is in the range of 0.03~0.3, n AIDS / n SiO2 The ratio is in the range of 0.001 to 0.01, crystallized at 150 to 200°C for 24 to 120 hours, and then quenched and recovered to obtain a filamentary low silicon-aluminum ratio ZSM-48 molecular sieve.

[0022] The synthesized ZSM-48 molecular sieve is exchanged with 0.1-1.0 mol / L ammonium ion solution at a solid-liquid ratio of 1:5-10 at 60-100 °C to prepare H-type ZSM-48 molecular sieve, which can be used as a catalyst active component, loaded with metal components and binders to prepare catalyst applications.

[0023] Furthermore, the ZSM-48 molecular sieve of the present invention can be prepared into a molecular sieve catalyst for use in the catalytic dewaxing reaction of paraffin-containing feedstocks, and can also be used in the fields of n-alkane hydroisomerization, long-chain alkane hydrocracking, C4-olefin cracking, xylene isomerization, methanol to gasoline (MTG), methanol to hydrocarbons and direct conversion of synthesis gas (CO+H2) to gasoline, and has good application prospects.

[0024] The invention has the beneficial effects of using waste FCC catalyst as a silicon-aluminum source and a specific low-cost organic template to synthesize a single crystal phase, a long bundle of filaments with good dispersibility in a short time, thereby reducing the synthesis cost and improving the synthesis efficiency. The invention synthesizes a low silicon-aluminum ratio ZSM-48 molecular sieve in the range of 24 to 100 silicon-aluminum ratio, and the unit molecular sieve contains a large amount of acid, which can break through the bottleneck that restricts the wide application of ZSM-48 molecular sieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 is the XRD phase diagram of the synthesized ZSM-48 molecular sieve in Example 1; Figure 2 is the XRD phase diagram of the synthesized ZSM-48 molecular sieve in Example 2; Figure 3 is the XRD phase diagram of the synthesized ZSM-48 molecular sieve in Example 3; Figure 4 is the XRD phase diagram of the synthesized ZSM-48 molecular sieve in Example 4; Figure 5 This is a SEM analysis diagram of the synthesized ZSM-48 molecular sieve in Example 1; Figure 6 This is a SEM analysis diagram of the synthesized ZSM-48 molecular sieve in Example 2; Figure 7 This is a SEM analysis diagram of the synthesized ZSM-48 molecular sieve in Example 3; Figure 8 This is the SEM analysis diagram of the ZSM-48 molecular sieve synthesized in Example 4. DETAILED DESCRIPTION

[0026] The embodiments of the present invention and the effects produced are further illustrated by examples and comparative examples, but the protection scope of the present invention is not limited to the contents listed in the examples.

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] The samples were characterized by XRD using a PANalytical Xpert Pro diffractometer with Cu Kα radiation (λ=0.15406 nm), a tube voltage of 45 kV, a tube current of 40 mA, a scanning range of 5°~55°, a step of 0.026°, and a step time of 17.34 ms.

[0029] The composition of the samples was determined using a PANalytical Axios series X-ray fluorescence spectrometer (XRF). The sample preparation method was the tablet pressing method, and the measurement conditions were an end window rhodium target, a tube voltage of 50 kV, and a tube current of 50 mA.

[0030] A Hitachi thermal field emission scanning electron microscope SU5000 was used for detection in the backscattering mode, with the beam current adjusted to “standard”, the accelerating voltage selected to 10 kV, and the magnification ranging from 5 k to 50 k.

[0031] The pore volume of the samples was measured on a Micromeritics ASAP2460 physical adsorption instrument. Before the test, the samples were vacuum treated at 200 °C for 6 h, and then the N2 adsorption and desorption isotherms were measured at liquid nitrogen temperature. The micropore volume of the samples was calculated by the t-plot method.

[0032] The relative crystallinity is calculated by the following method: Test the XRD of the sample to be tested and the standard sample respectively, calculate the characteristic peak area, and then substitute the following formula to calculate the relative crystallinity of the sample to be tested: Relative crystallinity = S 18-28° (Sample to be tested) / S 18-28° (standard sample) × 100%; Among them, S 18-28° (sample to be tested) is the area of ​​the characteristic peak of the sample to be tested at 2θ = 18-28°, S 18-28° (Standard sample) is the area of ​​the characteristic peak of the standard sample at 2θ=18-28°.

[0033] A Shimadzu inductively coupled plasma mass spectrometer ICPE-9820 was used, with bidirectional observation, spectrometer wavelength range: 167-800 nm, automatic sample injector: 68 positions, vacuum degree <10 Pa. Plasma gas: 8~20 L / min; auxiliary gas: 0.5~2 L / min; carrier gas: 0~2 L / min. Output stability: within ±0.1%.

[0034] The compositions of the FCC spent catalysts of Petrochemical Company A, Petrochemical Company B, Petrochemical Company C, Petrochemical Company D and Petrochemical Company E used in the following examples are shown in Table 1: Table 1 Composition of FCC waste catalyst from different sources

[0035] Example 1: Z48-1 1) The FCC waste catalyst particles of Petrochemical Company A were crushed and sieved to obtain small particles of 80-120 mesh, which were calcined at 650°C for 10 hours to remove carbon deposits and organic matter. The solid product after calcination was ultrasonically immersed in 0.15 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:10 at 60°C for 2 hours. The recovered material was filtered and washed with deionized water until the pH value reached 6-8. The filter cake was dried at 120°C for 24 hours, and the dry basis of the silicon-aluminum powder was 82%.

[0036] 2) 50.0 g of the silicon-aluminum material obtained in 1) was mixed with silica sol (Na2O% = 0.11%, SiO2% = 30.16%), NaOH (content 99%) and deionized water. SiO2 / n Al2O3 =25, n NaO2 / n SiO2 = 0.035, statically aged at 100 °C for 12 hours in a polytetrafluoroethylene liner, and [(CH3)3N + (CH2)6N + (CH3)3] ·2OH - (abbreviated as OSDA) and auxiliary ethanolamine (abbreviated as AIDS), so that nOSDA / nSiO2=0.035 in the synthesis system, n AIDS / n SiO2 =0.0075, n H2O / n SiO2 =20The liner was then covered and placed in a Parr Steel autoclave reactor, and the autoclave was then heated to 165°C for crystallization for 96 hours under static conditions, quenched and centrifuged to recover the solid product, washed with deionized water and dried at 120°C to obtain a solid product.

[0037] The obtained product was analyzed by powder XRD and SEM. The XRD pattern of the original powder after synthesis was shown in Figure 1 The SEM image of the product is shown in Figure 5 In the XRF analysis, the product showed a filamentous morphology, in which the diameter of the filaments was 1~2μm, the diameter of the single filament was 12~20nm, the length of the filaments was 3~12μm, and the dispersion was good. SiO2 / n Al2O3 The molar ratio is 24.8. The specific surface area and relative crystallinity data of BET and XRD analysis are shown in Table 1.

[0038] Example 2: Z48-2 1) The FCC waste catalyst particles of Petrochemical Company B were crushed and sieved to obtain small particles of 80-120 mesh, which were calcined at 750°C for 8 hours to remove carbon deposits and organic matter. The solid product after calcination was ultrasonically immersed in 0.25 mol / L sulfuric acid solution at 40°C with a solid-liquid ratio of 1:8 for 3 hours. The recovered material was filtered and washed with deionized water to a pH value of 6-8. The filter cake was dried at 110°C for 36 hours, and the dry basis of the silicon-aluminum powder was 83%.

[0039] 2) Mix 50.0 g of the silicon-aluminum material obtained in 1) with water glass (Na2O% = 10.68%, SiO2% = 29.7%), NaOH (content 99%) and deionized water. SiO2 / nAl2O3=40, n NaO2 / nSiO2 = 0.045, statically aged at 80 °C for 24 h in a polytetrafluoroethylene liner, and [(CH3)3N + (CH2)4N + (CH3)3] ·2OH - (OSDA abbreviation) and auxiliary agent N,N-dimethylethanolamine (AIDS abbreviation), so that the synthesis system n OSDA / n SiO2 =0.045, n AIDS / n SiO2 =0.0055, n H2O / n SiO2 =15The liner was then covered and placed in a Parr Steel autoclave reactor, and the autoclave was then heated to 175°C for crystallization for 72 hours under static conditions, quenched and centrifuged to recover the solid product, washed with deionized water and dried at 105°C to obtain a solid product.

[0040] The obtained product was analyzed by powder XRD and SEM. The XRD pattern of the original powder after synthesis was shown in Figure 2 The SEM image of the product is shown in Figure 6 In the XRF analysis, the product shows a filamentous morphology, in which the diameter of the filaments is 1~2μm, the diameter of the single filament is 10~20nm, the length of the filaments is 2~18μm, and the dispersion is good. SiO2 / n Al2O3 The molar ratio is 36.5. The specific surface area and relative crystallinity data of BET and XRD analysis are shown in Table 1.

[0041] Example 3: Z48-3 1) The FCC waste catalyst particles of Petrochemical Company C were crushed and sieved to obtain small particles of 80-120 mesh, which were calcined at 850°C for 6 hours to remove carbon deposits and organic matter. The solid product after calcination was ultrasonically immersed in 0.45 mol / L nitric acid solution at 25°C with a solid-liquid ratio of 1:6 for 5 hours. The recovered material was filtered and washed with deionized water until the pH value reached 6-8. The filter cake was dried at 130°C for 12 hours, and the dry basis of the silicon-aluminum powder was 85%.

[0042] 2) Mix 50.0 g of the silicon-aluminum material obtained in 1) with C-type silica gel (SiO2% = 95.18%), NaOH (content 99%) and deionized water. SiO2 / n Al2O3 =60, n NaO2 / n SiO2 = 0.045, statically aged at 120 °C for 12 hours in a polytetrafluoroethylene liner, and [(CH3)3N +(CH2)8N + (CH3)3] ·2OH - (OSDA abbreviation) and auxiliary agent N-methyl monoethanolamine (AIDS abbreviation), so that the synthesis system n OSDA / n SiO2 =0.08, n AIDS / n SiO2 =0.0085, n H2O / n SiO2 =35The liner was then covered and placed in a Parr Steel autoclave reactor, and the autoclave was then heated to 185°C for crystallization for 60 hours under static conditions, quenched and centrifuged to recover the solid product, washed with deionized water and dried at 115°C to obtain a solid product.

[0043] The obtained product was analyzed by powder XRD and SEM. The XRD pattern of the original powder after synthesis was shown in Figure 3 The SEM image of the product is shown in Figure 7 In the XRF analysis, the product shows a filament-like morphology, in which the diameter of the filament is 1~2μm, the diameter of the single filament is 10~20nm, the length of the filament is 4~20μm, and the dispersion is good. SiO2 / n Al2O3 The molar ratio is 58.4. The specific surface area and relative crystallinity data of BET and XRD analysis are shown in Table 1.

[0044] Example 4: Z48-4 1) The FCC waste catalyst particles of Petrochemical Company D were crushed and sieved to obtain small particles of 80-120 mesh, which were calcined at 950°C for 4 hours to remove carbon deposits and organic matter. The solid product after calcination was ultrasonically immersed in 0.85 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4 at 25°C for 2 hours. The recovered material was filtered and washed with deionized water to a pH value of 6-8. The filter cake was dried at 115°C for 24 hours, and the dry basis of the silicon-aluminum powder was 81%.

[0045] 2) 50.0 g of the silicon-aluminum material obtained in 1) was mixed with ethyl silicate (TEOS>99%), NaOH (content 99%) and deionized water. SiO2 / n Al2O3 =80, n NaO2 / n SiO2 = 0.065, statically aged at 105 °C for 24 hours in a polytetrafluoroethylene liner, and [(CH3)3N + (CH2)6N + (C2H5)3] ·2OH -(OSDA abbreviation) and auxiliary agent N-ethylethanolamine (AIDS abbreviation), so that the synthesis system n OSDA / n SiO2 =0.15, n AIDS / n SiO2 =0.0015, n H2O / n SiO2 =40The liner was then covered and placed in a Parr Steel autoclave reactor, and the autoclave was then placed under static conditions and heated to 195°C for crystallization for 36 hours, quenched and centrifuged to recover the solid product, washed with deionized water and dried at 120°C to obtain a solid product.

[0046] The obtained product was analyzed by powder XRD and SEM. The XRD pattern of the original powder after synthesis was shown in Figure 4 The SEM image of the product is shown in Figure 8 In the XRF analysis, the product showed a filamentous morphology, in which the diameter of the filaments was 1~2μm, the diameter of the single filament was 15~20nm, the length of the filaments was 3~16μm, and the dispersion was good. SiO2 / n Al2O3 The molar ratio is 76.8. The specific surface area and relative crystallinity data of BET and XRD analysis are shown in Table 1.

[0047] Example 5: Z48-5 1) The FCC waste catalyst particles of Petrochemical Company E were crushed and sieved to obtain small particles of 80-120 mesh, which were calcined at 1000°C for 2 hours to remove carbon deposits and organic matter. The solid product after calcination was ultrasonically soaked in 0.35 mol / L sulfuric acid solution at 20°C with a solid-liquid ratio of 1:6 for 3 hours. The recovered material was filtered and washed with deionized water to a pH value of 6-8. The filter cake was dried at 100°C for 24 hours, and the dry basis of the silicon-aluminum powder was 78%.

[0048] 2) 50.0 g of the silicon-aluminum material obtained in 1) was mixed with trimethoxysilane (purity> 99%), NaOH (content 99%) and deionized water. SiO2 / n Al2O3 =100, n NaO2 / n SiO2 = 0.078, static aging at 105 °C for 36 hours in a polytetrafluoroethylene liner, and [(CH3)3N + (CH2)6N + (CH3)3] ·2Br - (OSDA abbreviation) and auxiliary agent N, N-dimethylisopropanolamine (AIDS abbreviation), so that the synthesis system has n OSDA / n SiO2 =0.25, nAIDS / n SiO2 =0.0095, n H2O / n SiO2 =55The liner was then covered and placed in a Parr Steel autoclave reactor, and the autoclave was then heated to 155°C under static conditions for crystallization for 120 hours, quenched and centrifuged to recover the solid product, washed with deionized water and dried at 120°C to obtain a solid product.

[0049] The powder XRD analysis of the product was consistent with the product being pure ZSM-48 molecular sieve. SiO2 / n Al2O3 The molar ratio is 97.3. The specific surface area and relative crystallinity data of BET and XRD analysis are shown in Table 1.

[0050] Comparative Example 1: Preparation of Molecular Sieve VS-1 Aluminum sulfate, hexamethyldiamine hydroxide (HMBr), potassium hydroxide, and deionized water were mixed and stirred for 30 minutes before adding silica sol. The molar ratio of various substances in the mixed solution was n (Al2O3): (HMBr): n(Na+): n(H2O): n(SiO2) = 0.01: 0.03: 0.3: 5: 1. The mixture was transferred into a crystallization kettle and crystallized at 80°C for 24 hours, and then heated to 180°C for crystallization for 48 hours. After the crystallization was completed, the product was filtered and dried at 120°C for 6 hours. The sample was calcined at 600°C for 4 hours and determined to be ZSM-48 molecular sieve, and the molecular sieve was named VS-1. The XRF analysis results, specific surface area, and relative crystallinity data are shown in Table 1.

[0051] Comparative Example 2: Molecular sieve VS-2 was prepared according to the preparation method of the embodiment of patent CN17963939A Weigh 1g of sodium hydroxide and add it to 60g of deionized water. Stir until completely dissolved, then weigh 0.16g of sodium aluminate (Al2O3=39.95%, Na2O=31.15%) and add it to the mixed solution. After stirring for one hour, add 1.2g of urea until it is completely dissolved, then add 6.5g of hexamethylammonium bromide, stir vigorously for one hour, and finally add 15g of silica sol (SiO2=40wt%, Na2O=0.11%) dropwise. The gel mixture is placed at room temperature for dynamic aging for 12h and then transferred to the ultragravity crystallization device. The speed is set to 1000rpm and the temperature is 170℃ for crystallization for 72h. After cooling, washing and drying, the ZSM-48 molecular sieve raw powder can be obtained. The ZSM-48 molecular sieve raw powder is placed in a muffle furnace and roasted at 550℃ for 3h to remove the template to obtain the ZSM-48 molecular sieve. X-ray diffraction (XRD) test shows that it is pure phase ZSM-48 molecular sieve, and the silicon-aluminum ratio of the product is n SiO2 / n Al2O3=117, the molecular sieve is named VS-2, and the XRF analysis results, specific surface area and relative crystallinity data are shown in Table 2.

[0052] Comparative Example 3: Preparation of Molecular Sieve VS-3 The preparation process and silicon-aluminum source are the same as those in Example 1, except that the FCC waste catalyst particles of Petrochemical Company A are crushed and sieved to obtain small particles of 80-120 mesh, which are calcined at 650°C for 10 hours to remove carbon deposits and attached organic matter, and no subsequent acid ultrasonic treatment is performed. In addition, the auxiliary agent ethanolamine is not added. The mixed slurry is statically aged at 100°C for 12 hours and crystallized at 65°C for 96 hours. The silicon-aluminum ratio of the product is n SiO2 / n Al2O3 =102, and the molecular sieve was named VS-3.

[0053] Table 2 Catalyst performance parameters

[0054] Test Case Take 100g of the molecular sieves in Examples 1-5 and Comparative Examples 1-3 and 100g of alumina respectively, mix them thoroughly in a conical mixer, and then introduce the mixture into a twin-screw extruder produced in Weihai, Shandong to obtain a cylindrical catalyst sample with a size of φ2*4mm, dry it at 120°C for 24 hours, and calcine it at 540°C for 6 hours to obtain a carrier. The mass fraction of the molecular sieve in the carrier is calculated to be 50%.

[0055] Pour 1 gram of tetraammine dichloroplatinum (containing 55.8% Pt mass fraction) into 100 grams of deionized water and stir until uniform. Pour 100g of the carrier into the above solution and soak at room temperature for 4 hours. Subsequently, the above catalyst precursor was dried at 120°C for 4 hours. It was then calcined under a flow of air at a temperature of 450°C for 4 hours. The semi-finished catalyst was placed in a hydrogen atmosphere again and reduced at 400°C for 4 hours to obtain a catalyst. The catalysts in Test Examples 1-5 were named ISOC-1 to ISOC-5, respectively, and the catalysts obtained in Comparative Test Examples 1-3 were named VSC-1, VSC-2, and VSC-3, respectively.

[0056] The above catalysts were evaluated using the following evaluation methods: 50g of catalyst was loaded into a high-pressure hydrogenation reactor. The hydrocracking tail oil raw material was injected into the reactor from top to bottom for reaction, and the reaction conditions were shown in Table 3 below. After the reaction was completed, the total liquid product was collected, and the liquid yield was calculated, and then the liquid product was distilled to remove the light components less than 420 degrees, and the components greater than 420 degrees were collected for analysis and calculation to obtain the product yield, and the results are shown in Table 4.

[0057] Table 3 Reaction conditions

[0058] Table 4 Catalytic reaction evaluation results at 330℃

[0059] It can be seen from the results in Table 2 that the silicon-aluminum ratio of the ZSM-48 molecular sieve synthesized by the present invention is lower than 100, and the obtained ZSM-48 molecular sieve has high relative crystallinity and BET specific surface area. It can be seen from Tables 3 and 4 that the further prepared hydroisomerization catalyst can obtain a higher product yield in the hydrocarbon oil hydroisomerization reaction.

[0060] The above-mentioned embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A filamentary ZSM-48 molecular sieve, characterized in that: In the ZSM-48 bundled filament molecular sieve crystal, the diameter of the bundled filament is 1-2 μm, the length of the bundled filament is 2-20 μm, the diameter of the single filament in the bundled filament is 10-20 nm, and the molar ratio of silicon oxide to aluminum oxide is 24-100. The preparation steps include: 1) The FCC waste catalyst particles are crushed into small particles of 80-120 mesh, calcined at 600-1000°C for 1-10 hours, and the calcined solid is ultrasonically soaked in 0.1-1.0 mol / L hydrochloric acid, sulfuric acid or nitric acid solution at a solid-liquid ratio of 1: (4-10) for 1-5 hours, filtered, washed with deionized water until the pH value reaches 6-8, and dried to obtain silicon aluminum powder with a dry basis ≥75%; 2) mixing the silicon-aluminum powder obtained in 1) with a silicon source, an alkali source and deionized water, aging at 80-120° C. for 12-36 hours, adding an organic template agent OSDA and an auxiliary agent AIDS, crystallizing at 150-200° C. for 24-120 hours, and quenching and recovering to obtain the bundled filamentous ZSM-48 molecular sieve; Silicon is calculated as silicon oxide, aluminum is calculated as aluminum oxide, alkali source is calculated as sodium oxide, and n SiO2 / n Al2O3 20~100, n NaO2 / n SiO2 0.03~0.08, n H2O / n SiO2 15~60, n OSDA / n SiO2 0.03~0.3, n AIDS / n SiO2 0.001~0.01; The organic template is [(R1)3N + (CH2)n N + (R2)3]·2X - , R1 and R2 are each independently a C1-C5 straight chain alkyl group, n is an integer of 3-10, X - OH - , Cl - Br - ,I - At least one of; The auxiliary agent is any one or more of ethanolamine, N,N-dimethylethanolamine, N-methylmonoethanolamine, N-ethylethanolamine, and N, N-dimethylisopropanolamine.

2. The filamentary ZSM-48 molecular sieve according to claim 1, characterized in that: R1 and R2 are each independently methyl, ethyl, n-propyl or n-butyl, n is an integer from 4 to 8, and X is OH - , Cl - Br - or I - Any one of .

3. The filamentary ZSM-48 molecular sieve according to claim 2, characterized in that: R1 and R2 are methyl groups, and X is OH - Or Br - .

4. The filamentary ZSM-48 molecular sieve according to any one of claims 1 to 3, characterized in that: The silicon source is one or more of silica sol, water glass, C-type silica gel, macroporous silica gel, coarse-porous silica gel, fine-porous silica gel, white carbon black, chromatography silica gel, diatomaceous earth and organic silane.

5. The filamentary ZSM-48 molecular sieve according to claim 4, characterized in that: The organosilane is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, ethyltriethoxysilane, vinyltriethoxysilane, triethoxysilane, propyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane, methyltriethoxysilane, trimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, methyldimethoxysilane, isobutyltriethoxysilane, diisopropyldimethoxysilane, and isobutylisopropyldimethoxysilane.

6. The filamentary ZSM-48 molecular sieve according to claim 5, characterized in that: The organic silane is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, trimethoxysilane, and triethoxysilane.

7. The filamentary ZSM-48 molecular sieve according to any one of claims 1 to 3, characterized in that: The reaction mixture SiO2 / n Al2O3 25~100, n NaO2 / n SiO2 0.035~0.08, n H2O / n SiO2 15~55, n OSDA / n SiO2 0.035~0.25, n AIDS / n SiO2 It is 0.0015~0.0095.

8. Use of the filamentous ZSM-48 molecular sieve according to any one of claims 1 to 7 in hydrocarbon oil hydroisomerization reaction.

Citation Information

Patent Citations

  • Synthetic method of ZSM-48 molecular sieve with low silica-alumina ratio

    CN105967202A

  • JMZ-5 and JMZ-6, zeolites having SZR-type crystal structure, and methods of their preparation and use

    CN109843803A

  • Hydroisomerization catalyst and preparation method and application thereof

    CN113751060A

  • Rugby-shaped ZSM-48 molecular sieve and preparation method thereof

    CN117963939A

  • Dewaxing using a molecular sieve catalyst

    US20200063042A1